Green Human Resource Management as a Workforce Management Innovation to Support Sustainability and Poverty Reduction - Venesia, Venesia (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2026)
This study analyzes the effect of Green Human Resource Management (Green HRM), defined as environmentally oriented human resource practices, on sustainability and poverty reduction among employees of coffee shops in Pontianak. The study also examines the mediating role of sustainability in this relationship. A quantitative approach was employed utilizing a survey questionnaire administered to 150 respondents. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that Green HRM had a positive and significant effect on sustainability and on poverty reduction. However, sustainability did not have a significant effect on poverty reduction and therefore did not mediate the relationship between Green HRM and poverty reduction. These findings indicated that Green HRM directly contributed to employee welfare through capacity building, training, and environmentally friendly policies, while sustainability practices implemented by coffee shops were more focused on environmental aspects and had not yet produced tangible socio-economic impacts. Overall, the findings emphasized that Green HRM played a strategic role in supporting the welfare of coffee shop employees. In contrast, sustainability practices needed to be expanded to generate a more significant contribution to poverty reduction.